PENDIDIKAN MULTIKULTURAL DARI PERSPEKTIF H.M. RASJIDI - Daru Nur Dianna (Profetika: Jurnal Studi Islam, 2020)
This paper aims to study the concept of religious thought and tolerance according to Prof. H.M. Rasjidi which will be a fundamental discussion in the concept of multicultural education. The methodology in this research is a literature study of books by Prof. H.M. Rasjidi who has a discussion about the concepts of religion and tolerance. The primary source book in this study is «Empat Kuliah Agama Islam» and «Koreksi Terhadap Dr. Harun Nasution dalam Islam Ditinjau dari Berbagai Aspeknya». Prof. H.M. Rasjidi, provides clear boundaries in the theological aspects of how Muslims have the concept of being able to live with followers of other religions. Muslims can live well together in social and economic aspects, but not in blending religion or equating all religions. According to him, religious pluralism in multiculturalism concept in the sense of equating to all of religion is something that needs to be avoided.